Atorvastatin enhances the therapeutic efficacy of mesenchymal stem cells-derived exosomes in acute myocardial infarction via up-regulating long non-coding RNA H19. Issue 2 (22nd May 2019) - Huang, Peisen; Wang, Li; Li, Qing; Tian, Xiaqiu; Xu, Jun; Xu, Junyan; Xiong, Yuyan; Chen, Guihao; Qian, Haiyan; Jin, Chen; Yu, Yuan; Cheng, Ke; et al.
Abstract: Aims: Naturally secreted nanovesicles, known as exosomes, play important roles in stem cell-mediated cardioprotection. We have previously demonstrated that atorvastatin (ATV) pretreatment improved the cardioprotective effects of mesenchymal stem cells (MSCs) in a rat model of acute myocardial infarction (AMI). The aim of this study was to investigate if exosomes derived from ATV-pretreated MSCs exhibit more potent cardioprotective function in a rat model of AMI and if so to explore the underlying mechanisms. Methods and results: Exosomes were isolated from control MSCs (MSC-Exo) and ATV-pretreated MSCs (MSC ATV -Exo) and were then delivered to endothelial cells and cardiomyocytes in vitro under hypoxia and serum deprivation (H/SD) condition or in vivo in an acutely infarcted Sprague-Dawley rat heart. Regulatory genes and pathways activated by ATV pretreatment were explored using genomics approaches and functional studies. In vitro, MSC ATV -Exo accelerated migration, tube-like structure formation, and increased survival of endothelial cells but not cardiomyocytes, whereas the exosomes derived from MSC ATV -Exo-treated endothelial cells prevented cardiomyocytes from H/SD-induced apoptosis. In a rat AMI model, MSC ATV -Exo resulted in improved recovery in cardiac function, further reduction in infarct size and reduced cardiomyocyte apoptosis compared to MSC-Exo. In addition, MSC ATV -Exo promoted angiogenesis and inhibited the elevation of IL-6 and TNF-α in the peri-infarct region. Mechanistically, we identified lncRNA H19 as a mediator of the role of MSC ATV -Exo in regulating expression of miR-675 and activation of proangiogenic factor VEGF and intercellular adhesion molecule-1. Consistently, the cardioprotective effects of MSC ATV -Exo was abrogated when lncRNA H19 was depleted in the ATV-pretreated MSCs and was mimicked by overexpression of lncRNA H19. Conclusion: Exosomes obtained from ATV-pretreated MSCs have significantly enhanced therapeutic efficacy for treatment of AMI possibly through promoting endothelial cell function. LncRNA H19 mediates, at least partially, the cardioprotective roles of MSC ATV -Exo in promoting angiogenesis. Graphical Abstract: